2006
DOI: 10.1111/j.1478-3231.2006.01314.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci analysis of mice administered the methionine–choline deficient dietary model of experimental steatohepatitis

Abstract: These data indicate that experimental steatohepatitis is a polygenic disease with genes determining ALT, liver weight, and liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…Mice were sacrificed 3 days after the last injection. In the second model, Ccl5 -/-and WT mice (n = 12 mice per group) were fed a MCD diet (MP Biomedicals Europe) for 8 weeks, which is an established model of NASH (40).…”
Section: Methodsmentioning
confidence: 99%
“…Mice were sacrificed 3 days after the last injection. In the second model, Ccl5 -/-and WT mice (n = 12 mice per group) were fed a MCD diet (MP Biomedicals Europe) for 8 weeks, which is an established model of NASH (40).…”
Section: Methodsmentioning
confidence: 99%
“…A fuller understanding of the physiology of NAFLD and NASH has been impeded by the absence of an animal model that closely recapitulates the human condition. Although there are an increasing number of animal models of NAFLD, none of these models fully produces the metabolic profile in concert with the histological patterns seen in humans (20,32,47,49,57,63). The widely employed methionine-choline-deficient mouse (33) produces steatohepatitis and fibrosis, but in a metabolic context that is distinct from that of humans with NASH.…”
mentioning
confidence: 99%
“…Socs3 has also been demonstrated in several studies to be an important mediator of both murine and human NASH (Prpic et al 2003;Bergen et al 1999;Parekh et al 1998;Surwit et al 1997;Winzell and Ahren 2004;Livingston et al 1994;Surwit et al 1988;Tilg 2010;Sachithanandan et al 2010;Surwit et al 1995;Watson et al 2000). Previous studies have also identified other QTL for the metabolic syndrome in mice (Jiang et al 2005;Rangnekar et al 2006). In this study, we identified 14 QTL that are related to metabolic syndrome phenotypes, but we did not identify QTL for hepatic triglycerides.…”
Section: Discussionmentioning
confidence: 34%
“…HFHC diets have been extensively utilized for murine models of obesity, diabetes, and fatty liver. Mice fed this diet develop obesity and many of the components of the metabolic syndrome in a strain-specific manner (Minkina et al 2012;Jiang et al 2005;Becker et al 2004;Schmid et al 2004;Kobayashi et al 2004;Rangnekar et al 2006). In this study, A/J and C57BL/6J Positive "a" values indicate that at a locus, the homozygous C57BL/6Jt trait mean is greater than the mean of the A/J homozygotes.…”
Section: Discussionmentioning
confidence: 91%